Energy landscape of a Kv channel revealed by temperature steps while perturbing its electromechanical coupling - Bernardo I. Pinto-Anwandter; Carlos A. Z. Bassetto; Ramon Latorre; Francisco Bezanilla (Nature Communications)
Abstract Voltage-dependent potassium channels (Kv) play a crucial role in membrane repolarization during action potentials. They undergo voltage-dependent structural conformational transitions according to their distribution across their energy landscape. Understanding these transitions helps us comprehend their molecular function. Here, we used sudden and sustained temperature changes (Tstep) combined with different voltage protocols and mutations to dissect the energy landscape of the Shaker K+ channel. We used two mutations, ILT (V369I, I372L, and S376T) and I384N, that affect the coupling between the voltage sensor (VSD) and the pore domain (PD), to obtain the temperature dependence of VSD last transition and the intrinsic temperature dependence of the pore, respectively. Our findings support a loose or tight conformation of the electromechanical coupling. In the loose conformation, the movement of the VSD is necessary but not sufficient to efficiently propagate the electromechanical energy to open the pore. In contrast, this movement is effectively translated into pore opening in the tight conformation. Our results describe the energy landscape of the Shaker channel and how its temperature dependence can be modulated by affecting its electromechanical coupling.